Relationship between the Breakdown Strength and Low-frequency Dispersion of the Complex Permittivity of Polymeric Dielectrics; ICSD '07 - Gefle O. S.; Lebedev S. M.; Tkachenko S. N.; Pokholkov Y. P. Yuri Petrovich (2007, 2007)
The relationship between the low-frequency dispersion of the complex permittivity and the breakdown strength of polymeric dielectrics was studied in this work. It was found that the minimum of the voltage-time characteristic of polymeric dielectrics that were studied is related with the dispersion of the complex permittivity. This allows us to predict the dielectric strength of polymeric dielectrics by means of the dielectric spectroscopy method. Good agreement between the experimental results and the model predicted data was found